"Illegal Religious Activities" and Counter-Terrorism in China. Issue 2 (June 2021) - Zhang, Chi
Abstract: The fight against terrorism prompts governments to differentiate between "good" religious practices and the "bad" ones. The simplistic dichotomy of "good" and "bad" Muslims has led to a cascade of criticism, but a fallacy underlying this dualism remains underexplored. This paper examines the "no true Scotsman" fallacy that is prevalent in the political discourse surrounding terrorism and religion. It argues that China's attempt to counteract the essentialist assumption about Uyghurs leads to a reinforced "good-versus-bad" dichotomous categorization of Muslims, reflected in the binary of "normal" and "illegal" in China's religious policy. This is a major contribution to the existing literature on politics and religion because, theoretically, this paper applies the "no true Scotsman" fallacy and "good" and "bad" Muslims dichotomy to explain the relationship between politics and religion; empirically, it provides a rich overview of the political nature of religious policy in China.